UTILITY OF STOOL ANTIGEN TEST IN DIAGNOSIS AND PROGNOSIS OF HELICOBACTER PYLORI ASSOCIATED CHRONIC GASTRITIS FROM A TERTIARY CARE HOSPITAL, BALOCHISTAN - Sana, Fatima; Ahsan, Javeria; Shujjat, Umer; Iqbal, Hamid; Bashir, Saima; Ahmed, Azeema (Infectious Diseases Journal of Pakistan, 2022)
Background: International literature has shown various investigational modalities used for Helicobacter pylori (H. pylori) associated gastritis diagnosis and its therapeutic response to eradication regimen. But there is paucity of availability of local data on this important issue from Balochistan. Material and Methods: A cross-sectional observational study was carried out in The Pathology Department of The Combined Military Hospital Quetta from May 2021 to April 2022. Stool samples for H. pylori Antigen detection were received from all the clinically suspected cases of chronic gastritis irrespective of their gender, aged 2-60 years, which were later on confirmed by histopathology of gastric biopsy specimens. Results: Total, 1450 HpSAg tests were performed, out of which 411(28.34%) specimens were found positive in the study. Our tested population was mainly male (69%). Majority of them belonged to the age group between 31-50 years (46-43%). Mean age of the patients in our studied populace was 39.45±31.9 years. The risk factors associated with chronic gastritis among males was (72%) smoking and (75%) excessive caffeine intake, where as in females, (68%) stress, (74%) excessive NSAIDS use and (41%) prolonged usage of steroids were the main contributing factors. (61%) Unhealthy lifestyle, (49%) positive family history and (58%) chronic diseases were more or less in same the proportion in both genders. 63% patients were found negative on repeat testing by HpSAg after 04 weeks of complete therapy. Whereas 37% patients who remained positive were treated for another 2 weeks for complete eradication. Only 3% were still positive despite repeated eradication therapies indicating treatment failure. Conclusion: To conclude, HpSAg test is a rapid, easier, low cost, non-invasive and equally reliable test that not only aids in patient diagnosis but is invariably helpful in monitoring patient response to eradication therapy in resource poor settings. Keywords: Chronic gastritis, Helicobacter pylori (H. pylori), H. pylori Stool for Antigen test (HpSAg), Eradication therapy